METHODS OF ORGANIZING THE WORK OF THE CLASS LEADER - Mamarajabova Yulduz Chorshanbi qizi; Bobomurodov Sirojiddin (American Journals, 2023)
Methods of working with parents and improving their legal literacy, recreational and psychotherapeutic tasks, methods of organizing the first parents' class meeting are explained.
Keywords: Parents , Family , Family Code , Marriage , Legal literacy of family members